2018
DOI: 10.17821/srels/2018/v55i3/123059
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differentiation and Perceived Ease of Usage of Electronic Resources by University Students in Selected Private Universities in Nigeria

Abstract: The importance of electronic resources as the bedrock of provision of accurate, easy to access, relevant and, up-to-date information in learning and research cannot be over-emphasized. Through electronic resources’ use students have access to global resources for their academic activities. However, despite the potential benefit electronic resources holds for effective learning and research by students, studies have shown that their proper and maximum use is still a matter for discussion. This study, therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
3
1
Order By: Relevance
“…Therefore, it could be said that the determinants elements such as computer self-efficacy, perception of external control, computer anxiety, perceived enjoyment, and objective usability with exception of computer playfulness do not influence the gender of users. The results disagreed with previous studies that there is a relationship between gender and perceived ease of use of e-resources by students (Bassi and Camble, 2011; Ebijuwa, 2018; Ikolo, 2012). On the other hand, there is a significant relationship between gender and computer playfulness.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, it could be said that the determinants elements such as computer self-efficacy, perception of external control, computer anxiety, perceived enjoyment, and objective usability with exception of computer playfulness do not influence the gender of users. The results disagreed with previous studies that there is a relationship between gender and perceived ease of use of e-resources by students (Bassi and Camble, 2011; Ebijuwa, 2018; Ikolo, 2012). On the other hand, there is a significant relationship between gender and computer playfulness.…”
Section: Resultscontrasting
confidence: 99%
“…They concluded in their results that there is no statistically significant difference between males and females on the use of electronic resources and that the gap is negligible. On the contrary, Bassi and Camble (2011) and Ikolo (2012) revealed a statistical difference between male and female students’ attitudes, towards the use of electronic resources for their various information needs.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Therefore, the University Library is highly used by undergraduate students of the University. Similar result obtained by Ebijuwa and Mabawonku [25] showed that Science and Engineering students topped their respondents while male were 67.7% respondents, and students between ages 17 -25 accounted for over 85%. Table 2 presents the information on the utilization of the library.…”
Section: Demographic Characteristics Of the Respondentssupporting
confidence: 82%
“…Agboola and Bamigboye [24] revealed significant influence of level of study on library use in one of the three universities studied. In other studies, Ebijuwa and Mabawonku [25] found that age made relative significant contribution but gender and academic discipline did not. Oyedum [5] also found that course of study made significant relative contribution to the use of university libraries while Tolutope [19] revealed relative contribution of gender on utilization of library software.…”
Section: Demographic Characteristics Of the Respondentsmentioning
confidence: 82%
“…Examples include educational movies, databases, e-books, e-reports, online course materials, and websites. Ebijuwa (2018) stated that computers and mobile devices have made DRs readily available, and they cover a wide range of topics. Ngugi and Mberia (2014) stated that people, especially young adults, are spending more time reading digital materials due to the expanding number of DRs available today.…”
Section: Introductionmentioning
confidence: 99%